Multi-Criteria AHP Approach for Selecting Office Facility Vendors: Publish Journal - Efendi, Iskandar; Setyadi, Antonius (International Journal of Indonesian Business Review, 2025)
ABSTRACT Purpose – This study develops and validates a multi-criteria decision-making framework based on the Analytic Hierarchy Process (AHP) to support objective and transparent selection of office facility vendors. The framework aims to enhance procurement accountability and align vendor choice with organizational competency and compliance requirements. Methodology/approach – A quantitative, descriptive-analytic approach was applied using a case study at PT. XYZ. Expert judgments were elicited from procurement and facility management professionals to construct pairwise comparison matrices across predefined criteria (experience, certification, business licensing, and professional association membership). Individual judgments were aggregated using the geometric mean method, criterion weights were derived from the principal eigenvector, and consistency of judgments was assessed via Saaty’s consistency ratio. Sensitivity checks were performed to evaluate ranking robustness. Findings – It Results show that vendor experience carries the greatest relative weight, followed by certification, business licensing, and association membership. All pairwise comparison matrices satisfied the consistency threshold (CR < 0.10). The AHP framework produced a clear, reproducible vendor ranking and reduced reliance on ad-hoc or subjective decision criteria. Novelty/value – The paper contributes a validated, practical AHP model tailored for office facility procurement, addressing a documented gap in structured vendor assessment within the Indonesian corporate context. The framework is readily adaptable for organizations operating under high compliance and safety demands.